2012
DOI: 10.1017/s0007114512001602
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids and incident type 2 diabetes: a systematic review and meta-analysis

Abstract: The relationship between omega-3 polyunsaturated fatty acids (n-3 PUFA) from seafood (eicosapentaenoic acid, EPA; docosahexaenoic acid, DHA) or plant (alpha-linolenic acid, ALA) sources and risk of type 2 diabetes mellitus (DM) remains unclear. We systematically searched multiple literature databases through June 2011 to identify prospective studies examining relations of dietary n-3 PUFA, dietary fish and/or seafood, and circulating n-3 PUFA biomarkers with incidence of DM. Data were independently extracted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
220
4
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(247 citation statements)
references
References 60 publications
16
220
4
7
Order By: Relevance
“…In agreement with previous studies, n-3 fatty acids were not associated with the worsening of glycaemia or the risk of incident type 2 diabetes [15,25,37]. The DHA sufficiency index (ratio of 22:6n-3 to 22:5n-6) was associated with improved insulin sensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with previous studies, n-3 fatty acids were not associated with the worsening of glycaemia or the risk of incident type 2 diabetes [15,25,37]. The DHA sufficiency index (ratio of 22:6n-3 to 22:5n-6) was associated with improved insulin sensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…We could not see the beneficial effects of other antioxidants; eicosapentaenoic acid (59), or VE (63,65) with/without AA on FBS, this finding was similar to results obtained by previous metaanalysis in diabetics (13,101).…”
Section: Discussionsupporting
confidence: 89%
“…However, none of these studies found an association with incident type 2 diabetes either (7). Interestingly, these studies did not find an increased risk with higher concentrations in the studies from the U.S., suggesting that the higher risk could at least partly be related to the dietary assessment method (7).…”
mentioning
confidence: 91%
“…In animal models, the long-chain omega-3 PUFAs have also been shown to decrease insulin resistance (4), but the results from randomized controlled trials in humans have generally found little benefits on glucose-insulin homeostasis (5,6). In prospective studies, the association between fish or EPA + DHA intake and risk of incident type 2 diabetes has been mixed (7)(8)(9)(10); in studies in the U.S., the association has even been positive (7,8). The random error inherited in dietary assessment methods can attenuate associations in dietary studies and thus could explain the null findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation